Insights Into Persistent HIV-1 Infection and Functional Cure: Novel Capabilities and Strategies - Ta, Tram M.; Malik, Sajjaf; Anderson, Elizabeth M.; Jones, Amber D.; Perchik, Jocelyn; Freylikh, Maryann; Sardo, Luca; Klase, Zackary A.; Izumi, Taisuke (Frontiers in Microbiology, 2022)
Although HIV-1 replication can be efficiently suppressed to undetectable levels in peripheral blood by combination antiretroviral therapy (cART), lifelong medication is still required in people living with HIV (PLWH). Life expectancies have been extended by cART, but age-related comorbidities have increased which are associated with heavy physiological and economic burdens on PLWH. The obstacle to a functional HIV cure can be ascribed to the formation of latent reservoir establishment at the time of acute infection that persists during cART. Recent studies suggest that some HIV reservoirs are established in the early acute stages of HIV infection within multiple immune cells that are gradually shaped by various host and viral mechanisms and may undergo clonal expansion. Early cART initiation has been shown to reduce the reservoir size in HIV-infected individuals. Memory CD4+ T cell subsets are regarded as the predominant cellular compartment of the HIV reservoir, but monocytes and derivative macrophages or dendritic cells also play a role in the persistent virus infection. HIV latency is regulated at multiple molecular levels in transcriptional and post-transcriptional processes. Epigenetic regulation of the proviral promoter can profoundly regulate the viral transcription. In addition, transcriptional elongation, RNA splicing, and nuclear export pathways are also involved in maintaining HIV latency. Although most proviruses contain large internal deletions, some defective proviruses may induce immune activation by expressing viral proteins or producing replication-defective viral-like particles. In this review article, we discuss the state of the art on mechanisms of virus persistence in the periphery and tissue and summarize interdisciplinary approaches toward a functional HIV cure, including novel capabilities and strategies to measure and eliminate the infected reservoirs and induce immune control.